2021
DOI: 10.1007/s11031-021-09883-5
|View full text |Cite
|
Sign up to set email alerts
|

Expressive suppression as an obstacle to social change: Linking system justification, emotion regulation, and collective action

Abstract: Research on system justification theory suggests that justifying the societal status quo decreases negative emotions, leading to less collective action. In this investigation, we propose that the degree to which negative emotions mediate the link between system justification and collective action may depend upon whether individuals tend to suppress the expression of their negative emotions. We tested this hypothesis in the diverse socio-political contexts of Turkey, Israel, and the U.S. In one correlational st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 92 publications
0
18
0
1
Order By: Relevance
“…Given the extent of inequality in the world, one might be surprised by the relative rarity of protests, even among those who recognize injustice in society (Jost et al, 2017;Sengupta et al, 2017;Solak et al, 2021). Identifying social psychological and other factors that increase or decrease the likelihood of protest participation-especially under circumstances of political repression-is crucial for understanding and overcoming resistance to social change.…”
Section: Nazım Hikmet Turkish Poetmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the extent of inequality in the world, one might be surprised by the relative rarity of protests, even among those who recognize injustice in society (Jost et al, 2017;Sengupta et al, 2017;Solak et al, 2021). Identifying social psychological and other factors that increase or decrease the likelihood of protest participation-especially under circumstances of political repression-is crucial for understanding and overcoming resistance to social change.…”
Section: Nazım Hikmet Turkish Poetmentioning
confidence: 99%
“…A number of studies-again, conducted in Western, democratic countries-have found that the endorsement of system-justifying belief systems is associated with increased positive affect and decreased negative affect, including anger and moral outrage directed at the social system (e.g., Chapleau & Oswald, 2014;Jost et al, 2008;Harding & Sibley, 2013;Napier et al, 2020;Osborne et al, 2019;Rankin et al, 2009;Sengupta et al, 2017;Solak et al, 2021;Suppes et al, 2019;Wakslak et al, 2007). For example, Goudarzi et al (2020) observed that individuals in the United States who scored higher on a measure of economic system justification reported lower levels of negative affect and exhibited less physiological arousal associated with emotional distress while watching a video about homelessness, compared to individuals who were lower in economic system justification.…”
Section: Nazım Hikmet Turkish Poetmentioning
confidence: 99%
“…First, the majority of social psychological research conducted in the last ten years on collective action has mostly focused on the Gezi Park protests (e.g., Leach et al, 2016;Stewart et al, 2019;Uysal & Akfırat, 2021a). Only a few studies have been conducted on protests against sexism (e.g., Fischer et al, 2017;Uluğ, Odağ, & Solak, 2020), protests related to women's issues (Okuyan & Curtin, 2018), protests related to LGBTQ+ rights (Uysal et al, COLLECTIVE ACTION AND SOCIAL CHANGE IN TURKEY 7 2021), protests supporting religious groups' rights (e.g., Acar et al, 2021;Bükün, 2014), protests for improving the current conditions of one's ethnic group and for ethnic justice Bagci & Turnuklu, 2019;Tropp et al, 2021) and protests favouring freedom of expression (Solak et al, 2021).…”
Section: Antecedents Of Collective Actionmentioning
confidence: 99%
“…Examples of direct and indirect effects of anger on collective action can be found in several works carried out in Turkey (e.g., Akkuş et al, 2020;Ayanian et al, 2021;Aytaç et al, 2018;Bükün, 2021;Stewart et al, 2019). However, in a more recent work, Solak et al (2021) have demonstrated that the way individuals regulate their emotions shaped individuals' responses regarding commitment to protest behavior. Specifically, they found that system-based anger (e.g., anger regarding how things work in Turkey's system) mediated the association between system justification and collective action in those who suppress the expression of their emotions less frequently, but not in those who use expressive suppression more frequently in Turkey (see Studies 1 and 2).…”
Section: Collective Action and Social Change In Turkey 10mentioning
confidence: 99%
“…The work by Anna Stefaniak and colleagues demonstrates another important trend in the study of affect in socio-political systems, namely the transition from a strictly descriptive approach to a more interventionist one (Ford et al, 2018 ; Halperin et al, 2013 ; Halperin, Pliskin et al, 2014 ; Solak et al, 2021 ). Relying mainly on the building blocks of research on emotion regulation (Gross, 2013 ), in recent years scholars have started to study the way emotional change can lead to improvement in politics in general and intergroup relations more specifically.…”
Section: A Brief Overview Of the Papersmentioning
confidence: 99%